Female leadership in emergency situations. Pandemic Covid 19 in Peru - Llanos Zuloaga, Martha (2021)
The theme of female leadership is increasingly present in gender reflections and studies. Currently there is strong evidence about the enormous potential of women to assume responsibility conflict resolution and group management due to that dimension of humanistic leadership that characterizes women. The patriarchal system and machismo make a common front, but Women Resilience is demonstrated and consolidated worldwide. It is mainly in emergency and conflict situations that the leadership and resilience are manifested, with a level of organization and solidarity typical of women in situations of poverty and vulnerability. The Covid 19 has exposed many institutional problems, limited visions lacking knowledge of reality and others, but it has also highlighted the solidarity, and prompt response of women. As a Resilience researcher, as a witness of women as Educators, Promoters, mothers in the popular dining rooms, glasses of milk, pronoeis (Early childhood non-formal programmes) and so many social programs organized as community responses. I have to celebrate them and share the Peruvian example of the Popular Pots expanded to Latin America.